Arqueologia urbana: cultura material, patrimônio e história na cidade de Belém-PA - Azulai, Luciana Cristina de Oliveira (Brasiliana: Journal for Brazilian Studies, 2021)
The article addresses the recent history and contemporary challenges of urban Archeology, emphasizing the studies of material culture in the urban environment, its importance and peculiarities in the context of cities. It also presents relevant examples of urban archeology in Belém-PA and the observations and interpretations about the study carried out on the Museum of the Federal University of Pará-MUFPA and its collection of urban archeology that is under the custody of this institution, formed through traces found in the museum garden during the renovations carried out on the site. The conclusion focuses on the idea that these remains and the Museum itself and the palace that houses it, are part of an urban and historic site in Belém. Thus, it is intended to contribute to the discussions on archaeological material culture and its importance as part of history of the city.